Avascular Necrosis of Talus Diagnosed on Tc-99m MDP Bone Scan - Kamra, Ashish R (Indian J Nucl Med, 2017)
Avascular necrosis (AVN) of bone is defined as the cellular death of bone components due to the interruption of the blood supply; the bone structures then collapse, resulting in pain and loss of joint function. Magnetic resonance imaging (MRI) is the gold standard to diagnose AVN. We present an unusual case of AVN of talus in a patient of thalassemia major that was diagnosed on the Tc-99m MDP bone scan with equivocal findings on MRI. Key Message: The diagnosis of AVN is primarily done using radiological investigations. However, the bone scan plays a role in the diagnosis in atypical presentations and should be considered when MRI is equivocal.